Harvesting Benefits and Extensibility - Wubbel, John (JMP Connections, 2017)
A unique aspect about working with business intelligence (BI) data is that often subtle opportunities arise yielding benefits. Harvesting those benefits collectively across the enterprise raises a firm's competitive advantages. The BI metric is often extensible because in so many situations, its applicability can be replicated. Extensible means that the platform can be utilized by many other business departments within the enterprise. It also means that other workstations will only need JMP® on their workstations, not the entire platform as specified in this document. Configuration management version control (CMVC) may be a real possibility, a matter of practicality as a result of extensibility. For success not only with the enterprise metrics, but when others start adopting the work, there comes a time when controlling and managing the source code becomes a necessity. Putting the spreadsheet into the distributed version control system (DVCS) is really for the purpose of maintaining or monitoring it for structural changes.